In vivo Retinal Fluorescence Imaging With Curcumin in an Alzheimer Mouse Model - Sidiqi, Ahmad; Wahl, Daniel; Lee, Sieun; Ma, Da; To, Elliott; Cui, Jing; To, Eleanor; Beg, Mirza Faisal; Sarunic, Marinko; Matsubara, Joanne A. (Frontiers in Neuroscience, 2020)
Alzheimer’s disease (AD) is characterized by amyloid beta (Aβ) plaques in the brain detectable by highly invasive in vivo brain imaging or in post-mortem tissues. A non-invasive and inexpensive screening method is needed for early diagnosis of asymptomatic AD patients. The shared developmental origin and similarities with the brain make the retina a suitable surrogate tissue to assess Aβ load in AD. Using curcumin, a fluoroprobe that binds to Aβ, we labeled and measured the retinal fluorescence in vivo and compared with the immunohistochemical measurements of the brain and retinal Aβ load in the APP/PS1 mouse model. In vivo retinal images were acquired every 2 months using custom fluorescence scanning laser ophthalmoscopy (fSLO) after tail vein injections of curcumin in individual mice followed longitudinally from ages 5 to 19 months. At the same time points, 1-2 mice from the same cohort were sacrificed and immunohistochemistry was performed on their brain and retinal tissues. Results demonstrated cortical and retinal Aβ immunoreactivity were significantly greater in Tg than WT groups. Age-related increase in retinal Aβ immunoreactivity was greater in Tg than WT groups. Retinal Aβ immunoreactivity was present in the inner retinal layers and consisted of small speck-like extracellular deposits and intracellular labeling in the cytoplasm of a subset of retinal ganglion cells. In vivo retinal fluorescence with curcumin injection was significantly greater in older mice (11-19 months) than younger mice (5-9 months) in both Tg and WT groups. In vivo retinal fluorescence with curcumin injection was significantly greater in Tg than WT in older mice (ages 11-19 months). Finally, and most importantly, the correlation between in vivo retinal fluorescence with curcumin injection and Aβ immunoreactivity in the cortex was stronger in Tg compared to WT groups. Our data reveal that retina and brain of APP/PS1 Tg mice increasingly express Aβ with age. In vivo retinal fluorescence with curcumin correlated strongly with cortical Aβ immunohistochemistry in Tg mice. These findings suggest that using in vivo fSLO imaging of AD-susceptible retina may be a useful, non-invasive method of detecting Aβ in the retina as a surrogate indicator of Aβ load in the brain.